Efektivitas Pelaksanaan Pengawasan Oleh Dinas Lingkungan Hidup (DLH) Kabupaten Boyolali Terhadap Industri Berisiko Tinggi - Riyadi Riyadi; Waluyo Waluyo; Rosita Candrakirana (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
Supervision is one of the systematic activities of environmental management. In the latest provision, environmental management supervision is regulated in the Ciptaker Law and several government regulations regarding risk-based business licensing. This also has implications for environmental management efforts in businesses and / or industrial activities, especially those with a high level of risk, which requires environmental approval as one of the components of the permit. Based on this, the formulation in this study is how effective the implementation of DLH supervision on industries that have a high level of risk in Boyolali Regency. This Legal Research uses empirical methods with a descriptive approach and data collection techniques with interviews. Based on the results of the study, it was found that many high-level industries in Boyolali Regency do not yet have an AMDAL as an environmental approval document as stipulated in laws and regulations. Of course, this is a problem because it is contrary to laws and regulations which are also a benchmark for the lack of effective supervision carried out by DLH. The lack of effective supervision by DLH is due to several inhibiting factors such as the lack of PPLHD and the lack of compliance of those in charge of industrial activities. However, in addition to these obstacles, several efforts have also been made to improve the effectiveness of supervision.